STRATEGI MENINGKATKAN LOYALITAS KONSUMEN MAKANAN KHAS KOTA CURUP KABUPATEN REJANG LEBONG - Destri Sonatasia; Onsardi Onsardi; Ety Arini (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
The title of this study is the Strategy of Increasing Consumer Food Loyalty in Curup City, Rejang Lebong Regency (Case Study in "Henvian" Typical Food Industry). This research is based on the importance of strategies in increasing business and consumer loyalty to products sold.Strategies to increase business and consumer loyalty can be done with a SWOT analysis. Place of this research is the "Henvian" shop that sells typical Rejang lebong food. The method used in this study is descriptive qualitative. Informants in this study were people who were considered to know for certain about the HENVIAN Specialty Food Store in Curup City, Rejang Lebong Regency. The data analysis technique used in this study is a SWOT analysis to determine the strengths, weaknesses, opportunities and threats in a typical Rejang Lebong food business.The results of this study can be concluded that the internal factors that are the strength of the marketing strategy are the quality of the product that is good at a price affordable to the public and tourists, service that is friendly and responsive to consumer needs, as well as technological advancements that facilitate the promotion of business. Internal factors that are a weakness are often lack of stock, there are some products that do not meet the standard packaging, the product shelf life is short, employees do not use uniforms. External factors that become opportunities are a fairly high economic community, abundant raw materials while external factors that are a threat are the many competitors, an unstable economy, the price of basic needs increases. Based on the results of the SWOT analysis of internal and external factors, the strategy used is to improve product quality by improving the appearance of packaging and quality of content and quality of service by providing uniforms to employees and providing standards of service to consumers.